2015
DOI: 10.1002/anie.201506737
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Use of a Phosphonate Amidine to Generate an Anti‐Phosphoarginine‐Specific Antibody

Abstract: Protein arginine phosphorylation is a post-translational modification (PTM) that is important for bacterial growth and virulence. Despite its biological relevance, the intrinsic acid lability of phosphoarginine (pArg) have impaired studies of this novel PTM. Herein, we report for the first time the development of phosphonate-amidines and sulfonate-amidines as isosteres of pArg and then use these mimics as haptens to develop the first high affinity sequence independent anti-pArg specific antibody. Employing thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Recently, we showed that arginine phosphorylation occurs in B. subtilis wildtype cells that were stressed with diamide (Fuhrmann et al, 2015b). However, the underlying molecular mechanism of the induction of arginine phosphorylation is not known.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we showed that arginine phosphorylation occurs in B. subtilis wildtype cells that were stressed with diamide (Fuhrmann et al, 2015b). However, the underlying molecular mechanism of the induction of arginine phosphorylation is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Using a pArg specific antibody (Fuhrmann et al, 2015b), we observed that YwlE efficiently dephosphorylates McsB (Figure 5B). However, arginine phosphorylation of McsB can be detected under oxidative stress, indicating that YwlE is inactivated while McsB is active during these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually the reaction is carried out for 1-3 days [26,27], in a solution of DCM or acetonitrile (ACN), although it can also be performed in neat BTMS. As far as the reaction temperature is concerned it can be performed either at room temperature, in refluxing CH 2 Cl 2 [19,28,29], at higher temperatures [1,30,31], and also under microwave conditions [32][33][34]. At lower temperatures or shorter reaction times an incomplete transesterification was reported [35].…”
Section: Resultsmentioning
confidence: 99%